Schneeball-Wırbelgruppe learning model: improving students’ concept mastery and critical thinking - Akihary, Wilma; Lestuny, Carolina; Apituley, Patresia S. (Intelektual Pustaka Media Utama, 2024)
Good concept mastery through critical thinking using various approaches, models, strategies, and methods of learning German is essential for the Education 4.0 era. Therefore, this study aimed to analyze the concept mastery and critical thinking skills of German language students at Pattimura University using collaborative learning that combines SchneeballWirbelgruppe learning. A one-group pretest-posttest design with a sample of 13 second-semester students in the academic year 2019/2020 was used. Furthermore, an essay test was used as an instrument while the data was analyzed using descriptive methods (N-gain test) and inferential methods (paired t-test). The descriptive analysis showed that the concept mastery and critical thinking skills of students were in the high and moderate categories. The paired t-test results showed a difference between the pretest and posttest using Schneeball-Wirbelgruppe learning model. Therefore, collaborative learning has a positive impact on improving students’ concept mastery and critical thinking skills in learning phonology and morphology courses. As for the implications of this research, the Schneeball-Wırbelgruppe learning model is recommended as a learning model that can be applied to other concepts in German language learning.